2008
DOI: 10.4321/s0213-61632008000200003
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in response to war stress in hospital personnel: Does profession matter? A preliminary study

Abstract: ISRAELABSTRACT -Background and Objectives: To study gender differences and the impact of trauma on hospital personnel during war. In addition, to test the relationship between gender and PTSD symptoms via mediation model.Methods: A random sample of physicians, nurses and administrative staff (n = 106) that were assessed for demographics, and PTSD symptoms a month after the war between Lebanon and Israel erupted.Results: Women had higher IES-R scores in comparison to men (25.27 vs. 16.18). Gender differences we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Several earlier studies conducted among nurses and other staff members in general hospitals, in Israel (Ben-Ezra, Palgi, & Essar, 2007;Essar, Ben-Ezra, Langer, & Palgi, 2008;Cohen, 2008), in Bosnia and Herzegovina, and in the US claimed that working with traumatized clients often increases the level of personal stress, which is manifested through symptoms of STSD, PTSD, and/or burnout (Chen, Chen, Tsai, & Lo, 2007;Hyman, 2001;Lind, 2000). Most of those studies concluded that the particular impact that long-term-caring for terror/war and/or trauma victims has on the individual is determined by numerous factors, including geographic location vis-à-vis the traumatic event, gender, age, cultural, mentality and participants' profession and seniority at work (Essar et al, 2008). For example, one study found higher levels of stress among the nursing profession in comparison to social workers (both professions are considered feminine professions in the country of study) (Dekel, Hantman, Ginzburg, & Solomon, 2006).…”
Section: Secondary Traumatization Among Professionals and Para-profesmentioning
confidence: 99%
“…Several earlier studies conducted among nurses and other staff members in general hospitals, in Israel (Ben-Ezra, Palgi, & Essar, 2007;Essar, Ben-Ezra, Langer, & Palgi, 2008;Cohen, 2008), in Bosnia and Herzegovina, and in the US claimed that working with traumatized clients often increases the level of personal stress, which is manifested through symptoms of STSD, PTSD, and/or burnout (Chen, Chen, Tsai, & Lo, 2007;Hyman, 2001;Lind, 2000). Most of those studies concluded that the particular impact that long-term-caring for terror/war and/or trauma victims has on the individual is determined by numerous factors, including geographic location vis-à-vis the traumatic event, gender, age, cultural, mentality and participants' profession and seniority at work (Essar et al, 2008). For example, one study found higher levels of stress among the nursing profession in comparison to social workers (both professions are considered feminine professions in the country of study) (Dekel, Hantman, Ginzburg, & Solomon, 2006).…”
Section: Secondary Traumatization Among Professionals and Para-profesmentioning
confidence: 99%
“…Ron's study (2015aRon's study ( , 2015b suggested some explanations for high levels of PTS that were fund among the Philippines workers. For example: most of those workers had never experienced events such as wars or military operations; the fact that their job demanded that they continue functioning in a routine fashion increased the sense of stress, both during the event and after-wards; studies have claimed that working with traumatized clients and the exposure to traumatic events often decreases personal stress levels, manifested by PTS symptoms (Dekel & Hobfoll, 2007;Essar et al, 2008;Ron & Shamai, 2013;Ron & Shamai, 2011;Arvay, 2001) or death anxiety. Among the local workers, it seems that the PTS symptoms levels were lower than those among the Philippine workers.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of prolonged stress during the war on hospital personnel were found to be substantial. [14][15][16] The objective of this study was to check the dose-response model during exposure to prolonged war stress where the external traumatic stressors changed in magnitude over time. The hypothesis is derived from the dose-response model for PTSD symptoms [4][5][6][7][8][9][10][11] that states that the more severe the external stressor, the more severe the exhibition of traumatic symptoms will be.…”
Section: Discussionmentioning
confidence: 99%
“…The hospital itself also was targeted by missile, and 40 missiles landed within hospital vicinity. [14][15][16] Sample Thirteen special army administrative staff (SAAS) members from the Rambam Medical Center in Haifa attended seven intervention meetings during the war. These intervention meetings were conducted in order to relieve stress from the soldiers.…”
Section: Eventmentioning
confidence: 99%